Supplementation with selenium, iron, and vitamin E in calves under immunological challenge - Salles, Márcia S. V.; Figueiroa, Fábio J. F.; Bittar, Carla M. M.; Gomes, Viviani; Marques, Raquel S.; da Silveira, Julia A. G; Facury Filho, Elias J.; de Freitas, José Esler; Saran Netto, Arlindo (Frontiers in Animal Science, 2025)
IntroductionThe management and nutrition of young calves are important for the production system due to their great impact on future milk production potential. This study was to evaluate the performance and health of calves in the suckling phase, with supplementation of selenium, iron, and vitamin E while undergoing immunological challenge with Anaplasma marginale.MethodsAn experiment was conducted on an experimental farm using 42 newborn Holstein male calves, aged up to 60 days, in a completely randomized design, and they were assigned to the following three treatments: C (control milk replacer, N = 14); SeVitE (milk replacer supplemented with 0.6 mg organic selenium/kg + 100 IU vitamin E, N = 14); SeVitEFe (milk replacer supplemented with 0.6 mg organic selenium/kg + 100 IU vitamin E + 200 mg Fe chelate/kg, N = 14).ResultsSelenium, iron, and vitamin E intakes were higher in supplemented animals. The mean blood count of Anaplasma marginale was lower in supplemented calves compared to controls and increased with time after inoculation. Increased serum selenium was observed in supplemented calves, without vitamin E and iron changes. Plasma lactate concentration was lower in supplemented animals and those with SeVitEFe had lower urea concentration at 60 days compared to control. Treatments did not influence hematological parameters, while some only changed with the age of animals. Plasma glutathione peroxidase concentrations were higher in supplemented animals, with the interaction between treatment and time, where higher concentrations were observed at 40 days of experiment for supplemented calves compared to control. Treatments did not influence the performance of animals. Animals with SeVitEFe showed a lower incidence of diarrhea in the first thirty days of the experiment.DiscussionSupplementation of selenium, iron, and vitamin E showed effectiveness in improving the animals’ oxidative metabolism, altering biochemical and hematological parameters, and reducing the pathogens of Anaplasma marginale, and the incidence of diarrhea, but did not enhance the animals’ performance.